La contaminación ambiental en la ciudad de Loja, como referente para la re-creación de obras pictóricas - Montaño Granda, Ronald Anibal (2014)
Environmental pollution is evident in the problem posed by the present time is going global, national and local level, where man has become the main polluter and destroyer of their natural environment. The landscape genre personally, can transmit the aesthetic and plastic approaches has therefore been important to study and analyze the history of art, through works that are related to the subject and how this influences the contemporary context to gain an understanding of everyday reality. In addition to the paintings, the technique used is acrylic on canvas, veiling, melting tones and chromatic processing, etc. It is evident in all proposed, the pictorial issue raised, which will provide artistic and aesthetic to environmental pollution in the city of Loja used as pretext creative approach.